The Development Of The Partungko Naginjang Tourist Village Website - Ruth Deby Sarvalista; Herlina Jasa Putri Harahap (PT. Intelek Cendikiawan Nusantara, 2026)
This study aims to develop a website for the Partungko Naginjang Tourism Village equipped with multilingual features, specifically in Indonesian, English, and German. This study employed a qualitative descriptive research method using the development model by Richey and Klein, which consists of three stages: planning, development, and evaluation. Data for this study were obtained through observation, interviews, and documentation at the research site, Partungko Naginjang Tourism Village. The result of this study is a multilingual website that provides information about the profile and tourism in Partungko Naginjang Tourism Village. This website has undergone an evaluation phase in the form of validation conducted by experts in the aspects of information, systematics, interface design and navigation, and ease of use. Validation was conducted by experts in media and content/materials, with a media validation score of 88.8 (Good), an English validation score of 90 (Good), and a German validation score of 90 (Good).